Development of a bipolar electrostatic chuck module with a beam-array assembly using the multiple etching process. (8th November 2018) - Choi, Seungman; Wakabayashi, Kazuki; Takahashi, Kunio; Saito, Shigeki
Abstract: In this paper, we propose a successful fabrication method for a bipolar electrostatic chuck (ESC) device with a beam-array assembly, in order to achieve a fairly flat surface on the beam's tip. A fabricated bipolar ESC device is expected to clamp a curved dielectric object due to its elastically-deformable beams, which are compliant with an object's surface. As a fabrication process, the lithography technique including multiple etching processes against a single etching mask was performed to etch a three-layer material (conductor–dielectric–conductor). Due to the fairly flat surface of the beam's tip (figure04 ), sufficient adhesional contact area with the target object for a large adhesional force can be obtained. In order to understand the adhesion performance of the device, an experimental force curve was measured and partially compared with the theoretical adhesional force calculated using finite element analysis. The Pascal-expression for future work dealing with a large surface area was also calculated, corresponding to stacked prototype modules.